CORRELATION OF KNOWLEDGE OF COMORBID FACTORS AS A RISK FACTOR OF COVID-19 SEVERITY WITH BEHAVIOR RELATED TO COVID-19 PREVENTION IN MEMBERS OF CHRONIC DISEASE MANAGEMENT PROGRAM IN BANGKALAN - Tasya Nabila; George N Tanudjaja; Edwin Budipramana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Knowledge about COVID-19 is very important for everyone during this pandemic. This is related to efforts to break the chain of the spread of the Covid- 19 virus. Moreover, many deaths caused by this virus are experienced by many people with comorbidities.Research Objectives: This research study was conducted to know the relationship between knowledge of comorbid factors as the main risk factor for the severity of COVID-19 and behavior related to COVID-19 prevention among members of the Chronic Disease Management Program (PROLANIS) in Bangkalan Regency. Research Methods: This study uses quantitative methods. This type of research is observational with a cross-sectional. This sampling used a simple random sampling technique. And the data analysis used in this research is the Spearman correlation test. Research Results: From the results of the analysis, it is known that there is a relationship between knowledge about comorbid factors as the main risk factor for the severity of COVID-19 with behavior related to preventing COVID-19 among members of the Chronic Disease Management (PROLANIS) program in Bangkalan Regency, as evidenced by a p-value of 0.000 <0, 05. The correlation coefficient value of 0.619 is included in the strong category.Conclusion: meaning that there is a strong relationship between knowledge about comorbid factors as the main risk factor for the severity of COVID-19 and behaviors related to preventing COVID- 19 among members of the Chronic Disease Management (PROLANIS) program in Bangkalan Regency.